Moisture swing co2 sorbents with enhanced capacity and kinetics

JP2022159255A5Inactive Publication Date: 2025-03-28PALO ALTO RESEARCH CENTER INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022061749
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-07
Filing Date
2022-04-01
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing direct air carbon dioxide (CO2) capture processes face high energy consumption, inefficient temperature swings, competitive adsorption with water, and oxidative degradation, limiting their efficiency and scalability.

Method used

Development of moisture swing adsorbents with controlled polymerization and ion exchange to create porous crosslinked polymer networks with quaternary ammonium ions, enhancing surface area and pore properties for rapid CO2 capture and desorption.

Benefits of technology

The new adsorbents achieve higher trapping capacity, improved mass transfer kinetics, and extended lifetime, reducing energy consumption and costs, while maintaining stability under ambient conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide moisture swing sorbents having high surface area and improved pore characteristics, and a method to capture CO2.SOLUTION: A composition of matter includes: a porous cross-linked polymer network; quaternary ammonium ions in the cross-linked polymer network; and at least one counter ion in the cross-linked polymer network that is at least one of hydroxide or a counter ion capable of forming hydroxide upon reaction with water. A method to produce a porous material, includes polymerizing a compound containing quaternary ammonium and a cross-linker using controlled polymerization and ion exchange in the presence of at least one of hydroxide or a counter ion capable of forming hydroxide upon reaction with water. A method to capture CO2, includes employing a sorbent comprising quaternary ammonium ions in a porous cross-linked polymer network in an environment to adsorb CO2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] (Cross-reference of related applications) This application claims priority and benefits of U.S. Provisional Application No. 63 / 170,008, filed on 2 April 2021, which is incorporated herein by reference in its entirety.

[0002] (Field of invention) This disclosure relates to a moisture swing adsorbent, more specifically, a moisture swing adsorbent having a high surface area and improved pore properties. [Background technology]

[0003] Existing direct air carbon dioxide (CO2) capture processes have limited adoption due to their high costs, ranging from $100 to $1,000 per ton of CO2, and high energy consumption of 170 to 570 kJ / mol of CO2. This corresponds to the second law efficiency, where the comparison between the system's actual capture energy and the minimum possible capture energy ranges from 4 to 12 percent. One type of direct air capture typically involves the use of temperature swing adsorption (TSA) processes using liquid or solid chemical or physical adsorbents.

[0004] These processes have several fundamental limitations that restrict the efficiency and process cost of CO2 capture at diluted ambient concentrations, due to the second law of adsorption. The high heat of adsorption required for selective CO2 uptake at 400 ppm, above 60 kJ / mol of CO2, necessitates large temperature swings. Parasitic sensible heat loading makes large temperature swings inefficient. Competitive adsorption between CO2 and water introduces additional limitations. Neutral amine adsorbents also suffer oxidative degradation.

[0005] Moisture swing adsorption represents one approach for direct air capture (DAC) that overcomes the limitations of TSA. MSA typically uses solid adsorbents containing quaternary ammonium (qAm). Quaternary ammonium can also be called quaternary amine. Compared to TSA adsorbents with non-hindered amines, MSA adsorbents operate at lower temperatures, and qAm adsorbents in MSA have a longer lifespan and better oxidation resistance. However, commercially available MSA adsorbents cause slow mass transfer kinetics. 2 These adsorbents have a small specific surface area of ​​less than 1 / g. These adsorbents have qAm groups embedded away from the polymer-air interface, resulting in low capacity utilization. MSA adsorbents with improved pore properties may exhibit faster cycle times and higher accessible capacity, but there is no approach to synthesizing them on a large scale. [Overview of the project]

[0006] A composition is provided having a porous crosslinked polymer network, a quaternary ammonium ion in the crosslinked polymer network, and at least one counterion in the crosslinked polymer network which is at least one of a counterion capable of forming a hydroxide upon reaction with hydroxide or water.

[0007] A method for producing a porous material is provided, comprising polymerizing a compound containing a quaternary ammonium and a crosslinking agent using controlled polymerization and ion exchange in the presence of at least one of hydroxides or counterions capable of forming hydroxides upon reaction with water.

[0008] A method for capturing CO2 is provided, which includes using an adsorbent containing quaternary ammonium ions in a porous crosslinked polymer network in an environment that adsorbs CO2. [Brief explanation of the drawing]

[0009] [Figure 1] A diagram of the moisture swing adsorption process is shown.

[0010] [Figure 2] This shows a graph of MSA aerogel.

[0011] [Figure 3] A flowchart of the stable free radical polymerization process is shown.

[0012] [Figure 4] A flowchart showing the modification of the process for forming MSA aerogel is shown. [Modes for carrying out the invention]

[0013] The embodiments herein exhibit disruptive performance over state-of-the-art moisture swing adsorption (MSA) adsorbents due to significant advancements in realization techniques for lifetime CO2 capture capacity. Lifetime CO2 capture capacity is a composite function of capacity, cycle rate, and lifetime that enhances the performance of MSA systems. The structure of the MSA adsorbents of the embodiments inherently reduces mass transfer barriers due to a substantial increase in surface area. The mesopore size enables rapid gas transport. The MSA adsorbents of the embodiments have better degradation resistance than other qAm (quaternary ammonium) adsorbents produced by post-synthetic modification. The embodiments have qAm groups covalently incorporated into the polymer backbone.

[0014] The novelty of the embodiments results from the controlled polymerization synthesis method used. Controlled polymerization of the aerogel enables structural properties optimal for carbon capture, including high surface area, thin pore walls, and mesoporosity. Additionally, the arrangement of different monomer residues in the polymer gel can be deliberately designed, allowing active qAm groups to be placed together within a block, and since two qAm groups need to be in proximity for CO2 desorption, this arrangement improves capacity. The spacing between qAm groups can also be adjusted by prepolymerizing segments of qAm with a comonomer or crosslinker in a selected ratio to achieve a block with a controlled average spacing of qAm groups. This arrangement also improves capacity, especially under different ambient sorption and desorption conditions.

[0015] The embodiments extend to novel aerogel adsorbents produced using PARC aerogel synthesis technology, methods of making aerogel adsorbents, and carbon capture modules / systems that utilize aerogel adsorbents. One embodiment is a method of capturing CO2 that includes using an adsorbent containing quaternary ammonium ions in a porous crosslinked polymer network in an environment that adsorbs CO2. Adsorption can occur at one of the ambient conditions or during active water or water vapor removal. The embodiments can include desorbing CO2 from the adsorbent, which can occur by one of the addition of water vapor, fog, mist, or liquid water. Additionally, desorption can occur at a temperature that is actively controlled higher than the adsorption. The adsorbent used in the process can be further specified by the description of the materials in this application.

[0016] Figure 1 shows a diagram of a general MSA process. In A, the process starts with an unloaded wet adsorbent. As the adsorbent dries and H2O evaporates, the adsorbent adsorbs CO2 in B 、 and is stabilized as bicarbonate. When the adsorbent dries and is loaded in C, the process generally transfers the adsorbent to the exhaust volume. Next, the adsorbent is wetted and CO2 desorbs from the adsorbent in D.

[0017] More specifically, in the MSA process using qAm groups, carbonate ions (CO3 2- ) bound to two qAm groups are stabilized by adsorbed water. CO2 adsorption occurs when the adsorbent dries naturally at a temperature of about 20 °C or around it under ambient conditions such as a relative humidity (RH) of about 20 - 50%. Other temperatures can be, for example, temperatures in the range of 0 - 20 °C, 0 - 80 °C, 0 - 70 °C, 0 - 40 °C, 15 - 40 °C, 15 - 30 °C, or any subset or combination of these ranges, and the pressure can be in the range of 0.04 kPa of CO2, 0.5 kPa of H2O, and 100 kPa of air. The process can be carried out at ambient temperature or at an actively controlled temperature. The process can be carried out at ambient humidity or at an actively controlled humidity. Drying causes the destabilization of the carbonate in the reaction CO3 2- +H2O (吸着) →HCO3 - +OH - and the adsorption of CO2 in the reaction OH - +CO 2(g) →HCO3 - .

[0018] During drying, there is a net decrease in the adsorbed water when the hydration shell of HCO3 - becomes smaller than the hydration shell of CO3 2- . For desorption, the adsorbent is closed in a low vacuum to separate air. Desorption occurs in water or humidity, such as an environment with a relative humidity of more than 60%, more than 70%, more than 80%, more than 90%, or more than 95% RH, at 20 °C or around it, or at a high temperature. The temperature range can include, for example, 0 - 20 °C, 0 - 120 °C, 15 - 120 °C, 20 - 100 °C, 20 - 70 °C, 0 - 80 °C, 0 - 70 °C, 0 - 60 °C, 0 - 50 °C, 0 - 40 °C, 15 - 40 °C, 15 - 30 °C, or any subset of these ranges, and CO3 2-Restore its stability. The process can be carried out at ambient temperature or at an actively controlled temperature. The process can be carried out at ambient humidity or at an actively controlled humidity. In a single-stage process, water and CO2 are recovered for compression with 8 - 10 kPa of CO2, 30 kPa of H2O, and 1 kPa of air, resulting in a higher concentration than the input air or gas, for example, a CO2 purity of approximately 90% after water is removed. The cycle is promoted by absolute water vapor pressure rather than relative humidity. The process may use multiple stages to generate CO2 at a higher purity.

[0019] Embodiments involve the polymerization of a qAm-containing compound, such as 2-(methacryloyloxy)ethyl]trimethylammonium, 2-(acryloyloxy)ethyl]trimethylammonium, 3-(methacryloylamino)propyl]trimethylammonium, (3-acrylamidopropyl)trimethylammonium, diallyldimethylammonium (DADMA), vinylbenzyltrimethylammonium, or other trimethyl-ammonium functional monomers, and a porous stabilizing crosslinker, such as divinylbenzene (DVB), trimethylolpropane triacrylate, trimethylolpropane ethoxylate triacrylate, di(trimethylolpropane) tetraacrylate, dipentaerythritol penta- / hexa-acrylate, trimethacryladamantane, dipentaerythritol, trimethylolpropane trimethacrylate, divinylbenzene, phenylenedimethacrylate, phenylenediacrylate, and 1,6-hexanediol diacrylate, or perfluorohexanediol. In some embodiments, the crosslinker is hydrophobic. Such crosslinkers include molecules having fluorinated groups or aliphatic groups.

[0020] In some embodiments, comonomers are used. In some embodiments, the crosslinking agent contains a qAm group. In some embodiments, the comonomer or crosslinking agent is selected for its hydrophobicity or hydrophilicity to control the strength of its interaction with water. These residues may appear in the crosslinked polymer network and may include styrene, styrene compounds, n-vinylpyrrolidone, vinyl acetate, vinyl chloride, methacrylate, acrylate, methyl methacrylate, acrylonitrile, methyl acrylate, ethylene, propylene, dimethylsiloxane, fluorinated vinyl, acrylic, or methacrylic compounds, hexa-iso-fluoroisopropyl methacrylate, hexa-iso-fluoroisopropyl acrylate, 2,2,2-trifluoroethyl methacrylate, 2,2,2-trifluoroethyl acrylate, and 1H,1H,2H,2H-heptadecafluorodecyl methacrylate. In addition, additional monomer residues may include hydrophobic monomers containing at least one of a fluorinated group or an aliphatic group.

[0021] In some cases, the monomer may refer to any polymerizable species containing a crosslinking agent. In some embodiments, the mass fraction of the qAm-containing compound in the adsorbent is 5% to 90%, 20% to 70%, 50% to 70%, or 50% to 90%. In some embodiments, the qAm / g loading in the adsorbent is 0.1 to 6 mmol qAm / g adsorbent, 3 to 5 mmol qAm / g adsorbent, or 4 to 6 mmol qAm / g adsorbent. In one embodiment, at least 80 percent of the quaternary ammonium ions are directly bound to at least one other quaternary ammonium ion.

[0022] The circulating adsorption capacity is the difference in CO2 uptake between the adsorption state at 25°C, 1 bar atmospheric pressure, and 400 ppm CO2, and the desorption state, such as when immersed in liquid water at 25°C. In some embodiments, the circulating adsorption capacity exceeds 0.05 mmol / g, 0.1 mmol / g, 0.25 mmol / g, 0.5 mmol / g, 0.7 mmol / g, 1 mmol / g, 1.2 mmol / g, or 1.5 mmol / g.

[0023] To maximize weight capacity, the content of qAm-containing monomers can be maximized in the adsorbent. In addition, to minimize the content of atoms not involved in CO2 sorption, low molecular weight qAm monomers such as DADMA-Cl or 2-(acryloyloxy)ethyl]trimethylammonium chloride may be selected. In some embodiments, in the chloride ion exchange form, the molecular weight of the quaternary amine-containing monomer that gives rise to the quaternary amine functional group in the polymer may be less than 250 g / mol, 200 g / mol, 190 g / mol, 180 g / mol, or 170 g / mol.

[0024] The adsorbents of the embodiments will have unparalleled MSA performance due to the physical and chemical structure of the adsorbents resulting from PARC's patented porous polymer stable free radical polymerization (SFRP) described in several patents and published patent applications, including U.S. Patent No. 10,626,224 and U.S. Patent Publication No. 2020 / 0031977. An example of an aerogel is shown in Figure 2 and comprises a porous crosslinked polymer network having quaternary ammonium ions and at least one counterion.

[0025] In a typical SFRP gelation process, a precursor is dissolved in a solvent to form a precursor solution containing a stable free radical, an optional reducing agent, and an initiator. The precursor solution may also contain a quaternary ammonium-containing monomer, a crosslinking agent, and an optional other monomer in a solvent containing an initiator, a nitroxide mediator, and an optional reducing agent. The stable free radical in the form of a nitroxide mediator reversibly binds to the growth chain ends to form a “resting” chain. TEMPO-OH(C8H 17Nitroxides such as N2O2, nitroxide species derived from the decomposition of alkoxyamines, 4-hydroxy-TEMPO, TEMPO derivatives, TIPNO, TIPNO derivatives, chlorobenzyl-TIPNO, SG1, or SG1 derivatives (where chain growth occurs only when SG1 3-nitro-4-(also known as 2-oxopyrrolidine-1-yl) separates from the chain ends). The reaction proceeds as living polymerization, with a reduced likelihood of undesirable chain termination events and suppression of nanogel precipitates formed from back-biting reactions. To produce an aerogel, the SFRP is carried out in a porous template solvent at 100-125°C or 70-200°C for 6-48 hours, or longer than 1 hour. The solvated gel is then solvent-exchanged and allowed to dry in the surrounding environment.

[0026] One embodiment uses SFRP, but several embodiments use other types of controlled polymerization, including but not limited to atom-transfer radical polymerization (ATRP), nitroxide-mediated polymerization (NMP), and reversible addition-fragmentation chain-transfer (RAFT) polymerization. The crosslinked polymer network obtained from controlled radical polymerization may contain residual chemical moieties from polymerization. These may include nitroxides, chain transfer agents, thiols, TEMPO-OH, nitroxide species derived from the decomposition of alkoxyamines, 4-hydroxy-TEMPO, TEMPO derivatives, TIPNO, TIPNO derivatives, chlorobenzyl-TIPNO, SG1, SG1, thiocarbonylthio compounds, xanthanthates, trithiocarbonates, dithioesters, dithiocarbamates, dithiobenzoates, metal catalysts used in ATRP, copper, and iron.

[0027] In the patented version of the SFRP process at PARC, additional reagents are used to adjust the SFRP equilibrium to a more active state, generating nanogels of adjustable size. This is achieved by using a slowly degrading initiator such as dicumyl peroxide or tert-butyl peroxide to successively generate radicals and reducing agents such as acetol, gradually consuming excess free nitroxide. To ensure the proximity of qAm groups and the desorption requirements to increase adsorbent capacity, some embodiments of SFRP synthesis begin with controlled polymerization of DADMA or vinylbenzyltrimethylammonium oligomers, sometimes in the range of 2 to 10 units in length. Importantly, SFRP allows polymerization to be interrupted and restarted with temperature changes. Subsequent reactions with crosslinking agents in the organic phase will incorporate poly(qAm monomers) into a space-filling crosslinked polymer gel. The arrangement of qAm residues in short blocks allows pairs of qAm to form CO3 2- This ensures that it can bind to an anion.

[0028] In other cases, similar techniques can be applied to incorporate qAm groups into polymers, for example, by first polymerizing qAm with non-qAm monomers or crosslinking agents of desired concentrations, and then interrupting and restarting the polymerization.

[0029] In some embodiments, the adsorbent capacity is enhanced by preventing qAm groups distributed in the polymer chain from being adjacent at a specific random frequency. The polymerization interruptions brought about by SFRP and other controlled polymerization processes can enable block-like architectures in which blocks are either pure polymerized qAm monomers or statistical mixtures of polymerized qAm monomers and other monomers or crosslinking agents.

[0030] In the exemplary sequential synthesis shown in Figure 3, the water-soluble qAm monomer in Cl form (e.g., vinylbenzyltrimethylammonium chloride or DADMA-Cl,qAm-Cl) is polymerized in water or a water-alcohol mixture capable of dissolving both the monomer and the nitroxide mediator, as previously shown in the SFRPs of other anionic monomers, and the polymerization will be thermally interrupted. In Figure 2, the solid line represents polyammonium and the dashed line represents the crosslinking agent. As shown in the figure, CO2 is bonded to the polyammonium.

[0031] To achieve copolymerization of hydrophilic qAm monomers with hydrophobic crosslinking agents such as DVB, some embodiments use Cl - This involves ion exchange of the DADMA-Cl oligomer to an anion with lower hydrophilicity, and migration to organic solvents such as n-methylpyrrolidone, NMP, dimethyl sulfoxide, acetophenone, dimethylformamide, and xylene, further enabling the SFRP with DVB to form a gel. The solvent is selected so that it has a boiling point higher than the reaction temperature. OH - , HCO3 - , or CO3 2- Final ion exchange with anions present in the MSA process, such as hydroxyl or carbonate ions, followed by solvent exchange and ambient drying, yields an adsorbent aerogel, which can be used as a monolith or processed into a powder or structured adsorbent with or without a binder or substrate. Hydroxyl or carbonate ions remain present in the adsorbent aerogel.

[0032] Several alternative routes to polymer aerogels are outlined in Figure 4. Potential routes to the product may also include directly ion-exchanging the qAm-Cl monomer with anions involved in the MSA process and then copolymerizing with a crosslinking agent, or polymerizing qAm-Cl, ion-exchanging it with anions involved in the MSA process, and then restarting polymerization with a comonomer or crosslinking agent. The procedures and variations described herein will also be applicable to a variety of qAm-functional monomers and qAm-functional monomers having vinyl groups or terminal carbon-carbon double bonds.

[0033] An additional advantage of PARC's SFRP is that, compared to conventional SFRP polymers, it results in a robust aerogel composed of coarse, interconnected gas-permeable nanogel particles, which has better properties for MSA applications. Nanogel suppression leads to pore collapse or radical polymerization, and larger, denser nanogels reduce surface area. In MSA adsorbents, PARC's SFRP provides maximum enhancement to cycle rate by minimizing transport barriers, and the pore wall size derived from the nanogel size is thinner, resulting in a higher specific surface area with comparable porosity. Several embodiments are 100m 2 It exhibits a high specific surface area (exceeding 1 / g), mesopore diameters of 10-30 nm, and thin pore walls (approximately 10 nm), enabling rapid gas transport, bulk diffusion, and CO2 uptake. Synthesis uses a scalable process that does not involve expensive supercritical CO2, resulting in reduced costs and enhanced scalability.

[0034] Direct air capture of CO2 by aerogel adsorbents can be incorporated into capture systems or processes. In some embodiments, water vapor is used to facilitate desorption, while in others, liquid water is used in a spraying process or by immersing the aerogel adsorbent. Sometimes, heat, reduced pressure, or both are used to further accelerate desorption. In some embodiments, adsorption occurs under ambient conditions. In other embodiments, water is actively removed from the aerogel, for example, by heat, a fan, or a dehumidifier or air conditioning unit. In some embodiments, multiple desorption chambers are arranged in series. This arrangement can increase the pressure of desorbed CO2. The aerogel itself may be a powder or a structured monolith and may be self-supporting or held in shape by separate structural materials.

[0035] Embodiments of this specification involve adsorbents for carbon dioxide adsorption comprising quaternary ammonium ions in a porous crosslinked polymer network. The adsorbent adsorbs more carbon dioxide at high water vapor content or water vapor content greater than that of liquid water. The adsorbent may have quaternary ammonium groups classified together. The quaternary ammonium may be diallyldimethylammonium or trimethylammonium ions having hydroxides, carbonates, bicarbonates, phosphates, hydrogen phosphates, or dihydrogen phosphate counterions. Any counterion that is a hydroxide or can react with water to form a hydroxide will function. The crosslinked polymer network of the adsorbent may comprise a powder or a monolith, or it may comprise an aerogel.

[0036] The adsorbent may include a crosslinking agent which is a group comprising divinylbenzene, 1,6-hexanediol diacrylate, methyl, ethylpropyl, isopropyl, tri, tetra, penta, or hexa-acrylates and methacrylates, trimethylolpropane triacrylate, trimethylolpropane ethoxylate triacrylate, di(trimethylolpropane)tetraacrylate, dipentaerythritol penta- / hexa-acrylate, trimethacryladamantane, dipentaerythritol, trimethylolpropane trimethacrylate, phenylenedimethacrylate, phenylenediacrylate, and perfluorohexanediol diacrylate. In addition, the crosslinking agent may be hydrophobic and may contain at least one of a fluorinated group or an aliphatic group. 2 / g or more, 200m 2 Over 500m 2 It may have a surface area exceeding / g and an average pore diameter of 2-50 nm.

[0037] Embodiments may include methods for producing adsorbents using controlled polymerization such as SFRP (stable free radical polymerization), RAFT (reversible addition-cleavage chain transfer), ATRP (atomic transfer radical polymerization), or NMP (nitroxide-mediated radical polymerization, also known as SFRP), or stepwise polymerization. When polymerization is SFRP, additional additives such as reducing agents or radicals with high decomposition temperatures may also be used. Initiators may include thermal initiators, photoinitiators, peroxides, benzoyl peroxides, diacetyl peroxides, di-t-butyl peroxides, lauroyl peroxides, dicumyl peroxides, azo compounds, azobisisobutyronitrile (AIBN), phenylazotriphenylmethane, benzophenones, anthraquinones, camphorquinones, benzyl, and benzoin. Examples of reducing agents include reducing sugars such as glucose, reagents containing hemiacetal groups, hydroxyacetone, or enediol species derived from ketones and aldehydes such as ketose sugars and aldose sugars. During the process, oligomers of quaternary ammonium may be formed first and then reacted with a crosslinking agent.

[0038] The RAFT process typically uses chain transfer agents, usually thiocarbonylthio compounds such as dithioesters, thiocarbamates, and xanthanthates, to enable control of molecular weight and polydispersity during free radical polymerization. The process can result in low molecular weight distributions and, when applied to linear polymerization, pre-selected molecular weights. When applied to crosslinking systems, the process can result in high-surface-area porous materials, including porous materials with high specific surface area and narrow pore size distributions, similar to SFRP. The ATRP process typically uses transition metals and alkyl halide initiators as catalysts. Residual species are activated by the transition metal complex, generating radicals via an electron transfer process, and the transition metal is oxidized to a higher oxidation state. The number of initiators determines the number of polymer chains. It typically results in polymers with similar molecular weights and narrow molecular distributions when used in linear polymerization. When applied to crosslinking systems, the process can result in high-surface-area porous materials, including porous materials with high specific surface area and narrow pore size distributions, similar to SFRP. Nitroxide-mediated radical polymerization (also known as stable free radical polymerization) uses nitroxide initiators to generate polymers, typically resulting in well-controlled stereochemistry and very low dispersibility.

[0039] When using RAFT or ATRP, the chemical groups may remain in polymers derived from thiocarbonylthio compounds, xanthanates, trithiocarbonates, dithioesters, dithiocarbamates, dithiobenzoates, metal catalysts used in ATRP, copper, or iron. These materials may remain in the polymer via covalent or physical mechanisms, either as whole molecules or fragments derived therefrom.

[0040] Embodiments may include a system for capturing CO2 from ambient air containing an aerogel adsorbent. Adsorption may occur under ambient conditions by removal of activated water. Desorption may occur by the addition of water vapor, fog, mist, or liquid water. Desorption in the system may occur in multiple chambers arranged in series.

[0041] This specification, including the claims, abstract, and drawings, and all features disclosed in all steps of any method or process disclosed, can be combined in any combination, except for any combination in which at least some of such features and / or steps are mutually exclusive. Each feature disclosed in this specification, including the claims, abstract, and drawings, can be replaced by an alternative feature that serves the same, equivalent, or similar purpose unless otherwise specified.

[0042] It will be understood that variations of those disclosed above, as well as other features and functions, or substitutes thereof, may be combined into many other different systems or applications. Various alternatives, modifications, variations, or improvements not currently foreseen or anticipated may subsequently be made by those skilled in the art, but these are also intended to be included by this embodiment.

Claims

1. 1. A composition comprising: a porous crosslinked polymer network; quaternary ammonium ions in the crosslinked polymer network; and at least one counterion in said crosslinked polymer network that is at least one of a hydroxide or a counterion capable of forming a hydroxide upon reaction with water.

2. 2. The composition of claim 1, wherein the at least one counterion in the crosslinked polymer network capable of forming a hydroxide is one of bicarbonate, carbonate, phosphate, hydrogen phosphate, or dihydrogen phosphate.

3. 10. The composition of claim 1, wherein the porous crosslinked polymer network comprises residual chemical moieties from a controlled radical polymerization.

4. 4. The composition of claim 3, wherein the residual chemical moieties of the controlled radical polymerization are formed from at least one of nitroxides, chain transfer agents, thiols, TEMPO-OH, nitroxide species derived from decomposition of alkoxyamines, 4-hydroxy-TEMPO, TEMPO derivatives, TIPNO, TIPNO derivatives, chlorobenzyl-TIPNO, SG1, SG1, thiocarbonylthio compounds, xanthates, trithiocarbonates, dithioesters, dithiocarbamates, dithiobenzoates, metal catalysts used in ATRP, copper, and iron.

5. The composition of claim 1 , wherein the porous crosslinked polymer network comprises residues of at least one additional monomer.

6. 6. The composition of claim 5, wherein the residue of at least one additional monomer is formed from at least one of styrene, a styrenic compound, n-vinylpyrrolidone, vinyl acetate, vinyl chloride, methacrylate, acrylate, methyl methacrylate, acrylonitrile, methyl acrylate, ethylene, propylene, dimethylsiloxane, a fluorinated vinyl, acrylic, or methacrylic compound, hexa-iso-fluoroisopropyl methacrylate, hexa-iso-fluoroisopropyl acrylate, 2,2,2-trifluoroethyl methacrylate, 2,2,2-trifluoroethyl acrylate, and 1H,1H,2H,2H-heptadecafluorodecyl methacrylate.

7. 6. The composition of claim 5, wherein the residue of the at least one additional monomer comprises a hydrophobic monomer containing at least one of a fluorinated group or an aliphatic group.

8. 2. The composition of claim 1, wherein the quaternary ammonium ion comprises a diallyldimethylammonium, trimethylammonium ion, 2-(methacryloyloxy)ethyl]trimethylammonium, 2-(acryloyloxy)ethyl]trimethylammonium, 3-(methacryloylamino)propyl]trimethylammonium, (3-acrylamidopropyl)trimethylammonium, or a moiety resulting from polymerization of a trimethyl-ammonium functional monomer.

9. The composition of claim 1 , wherein the composition comprises a crosslinker.

10. 10. The composition of claim 9, wherein the crosslinking agent is one selected from the group consisting of divinylbenzene, 1,6-hexanediol diacrylate, methyl, ethylpropyl, isopropyl, tri, tetra, penta, or hexa-acrylates and methacrylates, trimethylolpropane triacrylate, trimethylolpropane ethoxylate triacrylate, di(trimethylolpropane)tetraacrylate, dipentaerythritol penta- / hexa-acrylate, trimethacryladamantane, dipentaerythritol, trimethylolpropane trimethacrylate, phenylene dimethacrylate, phenylene diacrylate, and perfluorohexanediol diacrylate.

11. 10. The composition of claim 9, wherein the crosslinker is hydrophobic and contains at least one of a fluorinated group or an aliphatic group.

12. The composition of claim 1 , wherein the crosslinked polymer network comprises an aerogel.

13. 13. The composition of claim 12, wherein the aerogel of the adsorbent may comprise one of a powder, a structured monolith, a self-supporting structure, or comprises a separate structural material.

14. The composition is 2 / g, more than 200m 2 / g or more than 500m 2 13. The composition of claim 1 having a surface area of ​​greater than 1.0 μm / g.

15. The composition of claim 1, wherein the composition has an average pore diameter of 2 to 50 nm.

16. 2. The composition of claim 1, wherein the mass fraction of the quaternary ammonium groups in the composition has a range of 5% to 90%, 20% to 70%, 50% to 70%, or 50% to 90%.

17. 2. The composition of claim 1, wherein at least 80 percent of the quaternary ammonium ions are directly bonded to at least one other quaternary ammonium ion.

18. 10. The composition of claim 1, wherein the quaternary ammonium ions in the crosslinked polymer network are derived from monomers having a molecular weight of less than 200 g / mol when the monomers are in chloride ion-exchanged form.